Modelling and simulation of dispersions of powder emissions from multiple sources with the mathematical model Pol 15sm - Budianu, Mihaela; Nagacevschi, Valeriu; Macoveanu, Matei (Journal of Environmental Engineering and Landscape Management, 2014)
Over the last decades, air pollution has become one of the greatest challenges negatively affecting human health and the entire environment, including air, water, soil, vegetation, and urban areas. Lately, special attention has been given to mathematical modelling for diffusion of pollutants in the atmosphere as a particularly effective and efficient method that can be used to study, control and reduce air pollution. The diversity of models developed by different research groups imposed a rigorous understanding of model types in order to apply them correctly according to local or regional problems of air pollution phenomenon. Tus the authors have developed and improved two mathematical models for dispersion of air pollutants. Tis paper presents a case study of dispersion of powders in suspension originating from 14 point sources that correspond to 5 economic agents in the agroindustrial area of Vaslui city using a computer simulation based on the mathematical model Pol 15sm, for multiple point sources of pollution, designed by the authors.